(untitled) (Studia Prawnicze / The Legal Studies, 2019)
Zasada jawności, jako jedna z podstawowych zasad procesu karnego, jest realizowana – z wyjątkami – w toku całego postępowania. Nie jest jednak jednoznaczne, czy ta zasada obejmuje tylko jawność zewnętrzną rozumianą jako dostępność procesu dla społeczeństwa, czy także jawność wewnętrzną. Ten drugi aspekt jawności oznacza głównie dostępność procesu dla stron i ich przedstawicieli. Artykuł został poświęcony problemowi ujętemu w pytaniu: czy zasada jawności obejmuje także jawność wewnętrzną? Przedmiotem opracowania była analiza poglądów doktryny w tym przedmiocie. W konsekwencji autor zaprezentował też własne zapatrywania poparte szeroką argumentacją. Konkluzja artykułu polega na sformułowaniu tezy o potrzebie włączenia jawności wewnętrznej do zakresu zasady jawności. The principle of openness, as one of the basic principles in criminal proceedings, is realised – with exceptions – in the course of the entire process. However, it is not clear, whether this principle includes only openness external, being a form of the availability to the public of the proceedings, or it includes openness internal too. This second aspect of the openness is mainly the availability process for the parties and their representatives. The article is devoted to the issue contained in question: does the principle of openness include also openness internal? The subject of the paper is the analysis of views of doctrine in this respect. The author focuses also on the presentation of his standpoints supported by broad argumentation. The conclusion of the paper is based on the formulation of the thesis on need to include openness internal to the scope of the principle of openness.